ASYMPTOTIC BEHAVIOR OF SOLUTIONS OF AN n-TH ORDER NONLINEAR O.D.E. - Rojas Romero, Santiago César (2003)
In this paper, we prove that the solution of nonlinear Ordinary Differential Equations (ODE), with continuous coefficients and non-linear terms tending to zero at infinity, have an asymptotic behavior similar to the solution of there corresponding linear equations.